Efficacy and safety of Orthokeratology in Moderate and High Myopia Patients at Vio Optical Clinic During Januari 2020- December 2022 : A Retrospective Study: Poster Presentation - Observational Research - Ophthalmologist - WENI PUSPITASARI; Ajeng Kartika Ayu Putri (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Orthokeratology (OK) lens causes flattening of the cornea to reduce refractive power temporarily. The purpose of the current study was to determine efficacy, defined in terms of refractive correction, and common adverse effects in Indonesian population. Methods : Objective: To evaluate the efficacy and safety of OK for myopia correction and visual acuity (VA) changes in moderate and high myopia patients at Vio Optical Clinic Grand Galaxy Bekasi during January 2020 – December 2022 Results : Methods: In this retrospective study, 129 eyes with moderate and high myopia met the inclusion criteria of this study. Each subject wore the lens for 8 to 9 hours while asleep. The efficacy and safety were assessed after 1, 4, and 12 weeks follow up. Result: All subjects divided into two groups: 106 eyes (82.2%) had moderate myopia and 23 eyes (17.8%) had high myopia. The median age was 18 years old (ranging from 5 - 45 years). The spherical equivalent of VA of two groups decreased significantly in 1 and 4 weeks compare to pre-lens (p<0.001). LogMar uncorrected visual acuity (UCVA) of two groups showed improvement in 1 and 4 weeks compare to pre-lens (p<0.001). There were no severe complication in moderate myopia patients. There were three subjects of corneal staining were recorded in high myopia Conclusion : This study indicates orthokeratology is a safe and effective to correct myopia. Using orthokeratology can improve UCVA within one week and one month after OK lens in moderate and high myopia patients. There were mild complication in high myopia patients.